Actor and Power Dimensions in Collaboration Management of the "Tour of Lake Toba" Musical Performance - Satria, Tri Danu; Haryono, Slamet; Utomo, Udi (Catharsis, 2023)
Tour of Lake Toba is a musical performance initiated by Rumah Karya Indonesia as the organizational institution responsible for this performance which is based on the idiom of traditional musical culture in the Lake Toba area. The Tour of Lake Toba musical performance has the theme Sira, which is an acronym for Sinergi Rasa. Sira in the lexicon of the North Sumatra Cultural region means salt brought by sira travelers or salt bearers from coastal areas to the highlands as an artifact of the exchange of objects and knowledge that occurred in the past. The aim of this research is to discuss the actor and power dimensions in the Tour of Lake Toba musical performance. The method used in this research is qualitative using a naturalistic approach. The research is discussed using Jo Hatch's rational organization theory approach. The research results show that the tour of Lake Toba musical performance involves various actors, both main actors and supporting actors. These actors create cooperation that produces a performance output that is bound by a cooperation agreement. From this agreement, a process emerged consisting of planning, organizing, mobilizing and supervising the musical performance tour of Lake Toba in the cities of Bandung, Jakarta, Yogyakarta and Solo. Rumah Karya Indonesia Institution builds a strong social network. These connections and relationships are used to obtain support, resources, and information. So this becomes a network that provides specific power in carrying out North Sumatran traditional performances on the island of Java.